ANALISIS:PENGARUH;DEMOKRASI TERHADAP;PERTUMBUHAN;EKONOMI INDONESIA;BAGIAN TIMUR - Vina Indriani; Melti Roza Adry (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
The;purpose of;this research is;to;know:and;analyze:>(1);The;influence of;democracy;on;the economic;growth;of;eastern;Indonesia. (2) Investment influence on the economic growth of eastern Indonesia. (3) The influence of education on economic growth in eastern Indonesia. (4) The influence of democracy, investment, and education jointly towards the;economic;growth;of;eastern;Indonesia.The variables used;in;this study were economic growth as a bound variable and democracy as a free variable, as well as investment and educational variables as control variables. The research used the 17 provincial data panel in eastern Indonesia in 2009-2017. Data is obtained from the Central Statistics agency.The analysis tool used in this study is a regression panel with the model chosen is the Fixed Effect Model. The results showed that: (1) democracy is positive and significant to the economic growth of Eastern Indonesia, (2) investments have positive and significant impact on the economic growth of Eastern Indonesia, (3) education Positive and significant influence on the economic growth of Eastern Indonesia, (4) Democracy, investment, and education jointly significantly]influencetheeconomic?growth/of/eastern Indonesia.